Evaluating LSTM models for grammatical function labelling - Do, Bich-Ngoc; Rehbein, Ines (15th International Conference on Parsing Technologies - proceedings of the conference, 2017)
To improve grammatical function labelling for German, we augment the labelling component of a neural dependency parser with a decision history. We present different ways to encode the history, using different LSTM architectures, and show that our models yield significant improvements, resulting in a LAS for German that is close to the best result from the SPMRL 2014 shared task (without the reranker).
Gesehen am 22.11.2023